Associations of rotational shift work and night shift status with hypertension: a systematic review and meta-analysis. Issue 10 (October 2017) - Manohar, Sandhya; Thongprayoon, Charat; Cheungpasitporn, Wisit; Mao, Michael A.; Herrmann, Sandra M.
Abstract : Background: The reported risks of hypertension (HTN) in rotating shift and night shift workers are controversial. The objective of this meta-analysis was to assess the association between shift work status and HTN. Methods: A literature search was performed using MEDLINE, EMBASE and Cochrane Database from inception through October 2016. Studies that reported odds ratios (OR) comparing the risk of HTN in shift workers were included. A prespecified subgroup analysis by rotating shift and night shift statuses were also performed. Pooled OR and 95% confidence interval (CI) were calculated using a random-effect, generic inverse variance method. The protocol for this study is registered with International Prospective Register of Systematic Reviews; no. CRD42016051843. Results: Twenty-seven observational studies (nine cohort and 18 cross-sectional studies) with a total of 394 793 individuals were enrolled. The pooled ORs of HTN in shift workers in cohort and cross-sectional studies were 1.31 (95% CI, 1.07–1.60) and 1.10 (95% CI, 1.00–1.20), respectively. When meta-analysis was restricted only to cohort studies in rotating shift, the pooled OR of HTN in rotating shift workers was 1.34 (95% CI, 1.08–1.67). The data regarding night shift and HTN in cohort studies was limited. The pooled OR of HTN in night shift workers in cross-sectional studies was 1.07 (95% CI, 0.85–1.35). Conclusion: Based on the findings of our meta-analysis, shiftwork status may play an important role in HTN, as there is a significant association between rotating shift work and HTN. However, there is no significant association between night shift status and risk of HTN. Abstract : Supplemental Digital Content is available in the text